Cultivating global celebrity: Bindi Irwin, FremantleMedia and the commodification of grief. Issue 1 (2nd January 2017) - Potter, Anna; Hill, Lisa
ABSTRACT: Bindi Irwin, daughter of the late Steve Irwin, the Australian conservationist and star of The Crocodile Hunter series, has been celebretised since birth. Now age 17, Irwin's winning performance in the 2015 US Dancing With the Stars extended her public profile from children's TV into a prime-time talent show with a global reach. This article considers the role played by mega-indie production company FremantleMedia in the globalisation of Irwin's celebrity and her seamless transition from child to adult star. Analysis of Dancing With the Stars, however, reveals that Irwin's role in constructing a narrative of grief is integral to the effective exploitation of the Irwin family brands, including Australia Zoo. It demonstrates also how the emotional labour performed by Irwin in Dancing With the Stars, alongside the physical labour required for competition-level dancing, was key to her success and, in turn, the amplification of her celebrity in global media markets.